A Review on Error Analysis Stages in Teaching English Structure - Evi Agustinasari; Tiur Simanjuntak; Muhammad Bambang Purwanto (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
The goal of this research is to determine the role of error analysis in teaching English as a foreign language, particularly English Structure. Error analysis can provide information on a student's progress in learning a target language, which is then used to improve the teaching process so that they could still properly use the language. The method used is qualitative and descriptive research design. This research focuses on students of Politeknik Negeri Sriwijaya. Error analysis is essential for teachers to improve the quality of teaching. By doing so, the teacher owns information to improve the methodology including syllabus, teaching material and teaching techniques. The findings are four main stages of error analysis simplified in this study. They are detecting, locating the errors, describing the errors, and classifying the errors. First stage is done by gathering suspected errors; meanwhile works with unwanted errors are rejected or put aside. Then, locating the errors found on students' works were done by identifying them without considering types of the errors. Next step is describing errors where the errors are labeled based on the linguistic category. Final stage is error classification involving classification and counting errors. Each stage gives detailed information of students’ performance which is beneficial for the teachers to improve the quality of teaching including the material and how to deliver.